2008
DOI: 10.1523/jneurosci.0080-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Stimulation Induced Modulation of Spinal Locomotor Networks in Adult Spinal Rats

Abstract: The importance of the in vivo dynamic nature of the circuitries within the spinal cord that generate locomotion is becoming increasingly evident. We examined the characteristics of hindlimb EMG activity evoked in response to epidural stimulation at the S1 spinal cord segment in complete midthoracic spinal cord-transected rats at different stages of postlesion recovery. A progressive and phasedependent modulation of monosynaptic (middle) and long-latency (late) stimulation-evoked EMG responses was observed thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
123
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(131 citation statements)
references
References 41 publications
6
123
0
2
Order By: Relevance
“…To encourage locomotion via electrical spinal cord stimulation, rectangular pulses were delivered through L2 and S1 electrodes (40 Hz, 0.2 ms duration, 200-400µA) 9 . …”
Section: Electrochemical Neuroprosthesismentioning
confidence: 99%
“…To encourage locomotion via electrical spinal cord stimulation, rectangular pulses were delivered through L2 and S1 electrodes (40 Hz, 0.2 ms duration, 200-400µA) 9 . …”
Section: Electrochemical Neuroprosthesismentioning
confidence: 99%
“…It may provide a new therapeutic approach to complete SCI, as well as objective, electrophysiological proofs for the autonomous activity of lumbar CPG. Studies on both lab animals 61 and humans (a total of 10 patients) showed that low frequency electrical stimulation (2.2-50 Hz) with epidural electrodes elicited stepping-like movements; although a synergistic activation of kinematic chains (triple flexions alternating with extensions) was observed, it is obvious that a functional gait could not be achieved. 62,63 It should be noted that this technique involves some significant risks for the patient, such as infections, local hemorrhages, etc.…”
mentioning
confidence: 99%
“…The lack of effectiveness of electrical stimulation can be attributed to the filtering effect of CPG interneurons receiving synaptic inputs from the spinal rhythm generator to gate the flow of sensory information in the spinal cord (Sillar 1991). Interestingly, a better outcome is observed when stimuli are applied close to the spinal cord region, which putatively contains the CPG (Kiehn and Butt 2003), using epidural (Lavrov et al 2008a(Lavrov et al , 2008b or intraspinal (Gaunt et al 2006) electrodes.…”
mentioning
confidence: 99%